Design of Information System to Control Chemicals Inventory in Materials Laboratory - Yemima Putri Herlina (Eduvest - Journal of Universal Studies, 2025)
The material laboratory stores chemicals used for material testing. The storage of chemicals needs to be maintained as chemicals have a shelf life, and if stored for too long, they can be hazardous to both the environment and the individuals working in the material laboratory area. The current manual inventory management leads to overstocking or understocking, increasing storage costs. Therefore, this study aims to design an information system that shifts from manual to real-time, enhancing the effectiveness of inventory management and reducing storage costs. The PIECES method is used in this study because this method can analyze the current system's condition and the proposed system before implementation. System design is also employed in this study, such as use case diagrams, activity diagrams, and class diagrams, to clarify the communication flow within the material laboratory. The use of system design can demonstrate a structured communication flow in the material laboratory, enabling real-time information systems. The PIECES method helps researchers analyze the current manual system and the real-time system that will be used.